2009
DOI: 10.1152/physrev.00005.2009
|View full text |Cite
|
Sign up to set email alerts
|

Reward Processing by the Opioid System in the Brain

Abstract: The opioid system consists of three receptors, mu, delta, and kappa, which are activated by endogenous opioid peptides processed from three protein precursors, proopiomelanocortin, proenkephalin, and prodynorphin. Opioid receptors are recruited in response to natural rewarding stimuli and drugs of abuse, and both endogenous opioids and their receptors are modified as addiction develops. Mechanisms whereby aberrant activation and modifications of the opioid system contribute to drug craving and relapse remain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
676
1
15

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 831 publications
(728 citation statements)
references
References 427 publications
17
676
1
15
Order By: Relevance
“…Accordingly, anatomical and pharmacological data show that local delta opioid receptors can modulate hippocampal activity. These receptors are abundantly expressed in the HPC (Le Merrer et al, 2009), primarily in GABAergic interneurons (Rezai et al, 2012;Scherrer et al, 2006;Svoboda et al, 1999), and their pharmacological activation on hippocampal slices was found to disinhibit principal glutamatergic cells via interneuron inhibition (Lupica, 1995). Moreover, enkephalins, among endogenous ligands of delta receptors, are released in the lateral perforant path, where delta receptor activation is required for high frequency-induced LTP (Bramham et al, 1991;Chavkin et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, anatomical and pharmacological data show that local delta opioid receptors can modulate hippocampal activity. These receptors are abundantly expressed in the HPC (Le Merrer et al, 2009), primarily in GABAergic interneurons (Rezai et al, 2012;Scherrer et al, 2006;Svoboda et al, 1999), and their pharmacological activation on hippocampal slices was found to disinhibit principal glutamatergic cells via interneuron inhibition (Lupica, 1995). Moreover, enkephalins, among endogenous ligands of delta receptors, are released in the lateral perforant path, where delta receptor activation is required for high frequency-induced LTP (Bramham et al, 1991;Chavkin et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Delta opioid receptors are expressed in the hippocampus (HPC), dorsal and ventral striatum, amygdala, and prefrontal cortex (Le Merrer et al, 2009;Scherrer et al, 2006), all key brain substrates for memory function (White and McDonald, 2002). Pharmacological data support the notion that stimulating or inactivating delta opioid receptors impacts memory performance, although the exact implication of delta receptor activity remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 The opioid system has three endogenous ligands, encoded by precursors such as preproenkephalin (PENK), prodynorphin and pro-opiomelanocortin. Similarly, there are three endogenous opioid receptors, delta, kappa and mu.…”
Section: Reward Circuitrymentioning
confidence: 99%
“…The endogenous opiate system consists of three classes of opioid receptors: m, k, and d; and their endogenous ligands, endorphin, enkephalin, and dynorphin (Le Merrer et al, 2009). The m-opioid receptor (MOR) mediates a wide variety of natural rewards, including hedonic 'liking' of highly palatable food (Pecina and Berridge, 2000).…”
Section: Introductionmentioning
confidence: 99%